Standardisation of a terminology for blockchains: Distributed ledger technology. Standardisation of a terminology for blockchains. - Wurster, Simone; Ron, Eyal; Hofmann, Frank (Journal of Standardisation, 2024)
Blockchain technology is a revolutionary approach in the context of decentralised data systems. Starting with the introduction of the cryptocurrency Bitcoin, it has seen rapid growth in importance and investment. The clarification of basic terminology is particularly relevant for this young field of technology. To this end, the BlockOne project is developing a terminology specification based on the accelerated DIN-SPEC process. This article presents the method developed to prepare the terminology and the current status of the standardisation work.